2018
DOI: 10.1080/01621459.2017.1285775
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Population Size Estimation From Respondent-Driven Sampling: A Network Approach

Abstract: Estimating the size of stigmatized, hidden, or hard-to-reach populations is a major problem in epidemiology, demography, and public health research. Capture-recapture and multiplier methods are standard tools for inference of hidden population sizes, but they require random sampling of target population members, which is rarely possible. Respondent-driven sampling (RDS) is a survey method for hidden populations that relies on social link tracing. The RDS recruitment process is designed to spread through the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 78 publications
0
46
0
1
Order By: Relevance
“…5 and 6. This trained architecture aims to classify the data for an expected size and then it would be compared to the size calculated by COCOMO2 but when the SVM return multiple sizes then the proposed architecture utilizes SVM for the conflicted classes [25]. Table 2 represents the numeral value analysis of the proposed architecture with a varying number of neuron validations.…”
Section: Regression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…5 and 6. This trained architecture aims to classify the data for an expected size and then it would be compared to the size calculated by COCOMO2 but when the SVM return multiple sizes then the proposed architecture utilizes SVM for the conflicted classes [25]. Table 2 represents the numeral value analysis of the proposed architecture with a varying number of neuron validations.…”
Section: Regression Analysismentioning
confidence: 99%
“…Crawford et al in 2015][25] has shown the method of utilizing network data being analyzed by RDS (Respondent-driven sampling) for the estimation of hidden population size. The researchers have used an effective Bayesian technique for the integration of missing edges for employed subgraph individuals.…”
mentioning
confidence: 99%
“…Finally, we recommend that researchers design their data collections—both from the frame population and the hidden population—so that size estimates from the generalized scale-up method can be compared to estimates from other methods (see e.g., Salganik et al (2011a)). For example, if respondent-driven sampling is used to sample from the hidden population, then researchers could use methods that estimate the size of a hidden population from recruitment patterns in the respondent-driven sampling data (Berchenko et al, 2013; Handcock et al, 2014, 2015; Crawford et al, 2015; Wesson et al, 2015; Johnston et al, 2015). …”
Section: Recommendations For Practicementioning
confidence: 99%
“…With some notable exceptions, RDS has often been found to be cost‐effective for sampling hidden populations and the popularity of RDS has led to a wealth of new data (Malekinejad et al, ). The performance of the inferential component of the RDS package, however, is far more vulnerable to criticism than the sampling component (Guntuboyina et al, ; Crawford et al, ).…”
Section: Introductionmentioning
confidence: 99%